Communication strategies to promote the uptake of childhood vaccination in Nigeria: a systematic map. Issue 1 (1st December 2016) - Oku, Afiong; Oyo-Ita, Angela; Glenton, Claire; Fretheim, Atle; Ames, Heather; Muloliwa, Artur; Kaufman, Jessica; Hill, Sophie; Cliff, Julie; Cartier, Yuri; Bosch-Capblanch, Xavier; Rada, Gabriel; et al.
Abstract : Background: Effective communication is a critical component in ensuring that children are fully vaccinated. Although numerous communication interventions have been proposed and implemented in various parts of Nigeria, the range of communication strategies used has not yet been mapped systematically. This study forms part of the 'Communicate to vaccinate' (COMMVAC) project, an initiative aimed at building research evidence for improving communication with parents and communities about childhood vaccinations in low- and middle-income countries. Objective: This study aims to: 1) identify the communication strategies used in two states in Nigeria; 2) map these strategies against the existing COMMVAC taxonomy, a global taxonomy of vaccination communication interventions; 3) create a specific Nigerian country map of interventions organised by purpose and target; and 4) analyse gaps between the COMMVAC taxonomy and the Nigerian map. Design: We conducted the study in two Nigerian states: Bauchi State in Northern Nigeria and Cross River State in Southern Nigeria. We identified vaccination communication interventions through interviews carried out among purposively selected stakeholders in the health services and relevant agencies involved in vaccination information delivery; through observations and through relevant documents. We used the COMMVAC taxonomy to organise the interventions we identified based on the intended purpose of the communication and the group to which the intervention was targeted. Results: The Nigerian map revealed that most of the communication strategies identified aimed to inform and educate and remind or recall . Few aimed to teach skills, enhance community ownership, and enable communication . We did not identify any intervention that aimed to provide support or facilitate decision-making . Many interventions had more than one purpose. The main targets for most interventions were caregivers and community members, with few interventions directed at health workers. Most interventions identified were used in the context of campaigns rather than routine immunisation programmes. Conclusions: The identification and development of the Nigerian vaccination communication interventions map could assist programme managers to identify gaps in vaccination communication. The map may be a useful tool as part of efforts to address vaccine hesitancy and improve vaccination coverage in Nigeria and similar settings.